Understanding The Levels of Productivity of Teachers Who Are Exposed to In-Service Training - Ogunbayo, Shakirat Bola; Fatai, Ogunbayo Babatunde (Asian Journal of Assessment in Teaching and Learning, 2022)
The need for increased teacher productivity has become widely recognized, as is the fact that it depends on efficient and effective in-service training. In-service training is founded on the idea that teachers’ skills must be strengthened for schools to grow. This study compares the productivity levels of teachers exposed to in-service training and those without training. A field survey was conducted among teachers in selected secondary schools in Akowonjo Education District Lagos-State, Nigeria. A simple random sampling technique was employed for this study, and questionnaires were distributed to 80 subject teachers within the selected secondary schools. Demographic profiling, descriptive statistics, Pearson product-moment correlation, and T-test statistics were used to analyze the data collected. The study’s findings demonstrated that teacher productivity is determined by in-service training. The study also revealed that teachers who participate in the training program are more likely to perform well than those who do not. The study concluded that the government should establish a body that will constantly assess and evaluate teachers’ productivity levels after training and should always reward them appropriately for excellent performance.